Living Qurâ€™an dan Hadis di MI Nurul Ummah (Rutinitas, Ritual Ibadah dan Pembinaan Akhlak) - Assingkily, Muhammad Shaleh; Arif, Mahmud; Marhumah, Marhumah; Putro, Khamim Zarkasih (AR-RIAYAH: Jurnal Pendidikan Dasar, 2020)
This article examines the living Qurâ€™an and hadith through programmatic activities in madrasah ibtidaiyah (MI). During this time, the study of living Qurâ€™an and hadith is dominated by the area of social research, both within the scope of certain communities and the wider community. In fact, this study is important to be developed in educational institutions, as an effort to restore the â€œspiritâ€ of Islamic education and to make the Al-Qurâ€™an hadith â€œliving textâ€ in MI. For this reason, this study analyzes al-Qurâ€™an hadith learning and and programmed activities at MI Nurul Ummah. The main data was obtained through interviews, observations and study of documents focused on routines, rituals, and moral guidance in MI. The focus of these activities, in terms of oral, aural, writing, and attitude aspects. Thus, fulfilling the four aspects of something is referred to as the effort to live the Qurâ€™an and hadith.